Lao PDR : Country Procurement Assessment Report - World Bank (World Bank, Washington, DC, 2013)
The Government of Laos has made significant strides over the last eight years in improving its public procurement process, principally through the introduction of a procurement law and implementing rules and regulations that were facilitated by significant technical assistance from the Asian Development Bank. However, as this report illustrates, more remains to be done to improve the efficiency of public spending at a time when the country of Laos is still experiencing fiscal imbalances caused largely by the economic crisis of the late 1990s and the subsequent heavy burden of budget subsidies. This report contributes to the Government's ongoing economic and fiscal reform agencies. It analyzes strengths and weaknesses in the system and outlines an action plan to bring public procurement infurther into line with internationally accepted best practice. Implementation of the action plan is important not only in continuing to improve the effectiveness of public spending and attracting continued support for the Government's econoic reform program, but also in light of additional pressures arising from the Government's policy of decentralizing responsibilities for project formulation and implementation. The World Bank is making continued public procurement reform a key part of its Country Assistance Strategy for Laos. The Government's continued progress in improving its procurement system will help reduce the environment of high fiduciary risk.